If f(x)=x^2 + 2x +3f(x)=x2+2x+3, then how do you find f(a-1)?

2 Answers
May 28, 2016

a^2+2a2+2

Explanation:

Substitute x = a-1 into function.

rArrf(a-1)=(a-1)^2+2(a-1)+3f(a1)=(a1)2+2(a1)+3

expand brackets and collect like terms.

rArr(a-1)^2+2(a-1)+3=a^2-2a+1+2a-2+3(a1)2+2(a1)+3=a22a+1+2a2+3

=a^2+2=a2+2

May 28, 2016

It is enough to substitute xx with (a-1)(a1).

Explanation:

It is enough to write (a-1)(a1) every time that you read xx.

f(a-1)=(a-1)^2+2(a-1)+3f(a1)=(a1)2+2(a1)+3

then it is just a matter of doing a bit of algebra

f(a-1)=(a-1)^2+2(a-1)+3f(a1)=(a1)2+2(a1)+3
=a^2-2a+1+2a-2+3=a22a+1+2a2+3
=a^2+2=a2+2.